Disney Princess comics collection. Volume one. - Anderson, Tom, approximately 1930-; Weiss, Bobbi J. G.; David, Peter (Peter Allen); Palomino, Cris; Kreider, Karen; Moore, John Blair; Geradts, Evert, 1943-; Mackie, Howard; Maine, Régis (Joe Books, 2015)
"This collection includes retellings of beloved Disney Princess films as well as original tales never seen on screen. They may be young, inexperienced and impetuous, but the stories in this book prove that even though they're not queens, princesses rule!"--Page 4 of cover